Young girl cotton picker - Dorothea Lange:::Creator::::::::::::
Young girl cotton picker drags a long cloth bag behind her in early morning at Arvin Farm Labor Camp. Lange's photographs influenced the development of documentary photography and humanized the consequences of the Great Depression.